Environmental crimes, legal protection of drinking water and its practical application in Argentina - Minaverry, Clara María (Universidad Nacional del Litoral, 2022)
Drinking water is a good which is essential to life, at the same time, to guarantee a healthy environment, it is crucial to assure the quality of life and the development of current and future generations. Healthy environment consists of a third,generation human right which is closely linked to the fulfilment of other human rights, such as the access to potable water. There is limited environmental criminal laws enacted in Argentina. Therefore, this impacts directly in the effective protection of the drinkable water. The general objective of the paper is to analyse national regulations related to the preservation of drinking water in the country previously mentioned. In addition, this is related to a selection of jurisprudential cases to evaluate whether its application is efficacious when in practice. The design of this study will be documental research. The fieldwork will be carried out at the Environmental Consultant which depends on the “Instituto de Ecología y Desarrollo Sustentable”, of the “Universidad Nacional de Luján”. In this place, consultations will be followed up by the population. To sum up, three specific cases linked to the drinking water will be analysed in this paper.